Beyond Categorical Perception: Gradient Lexical Tone Processing Revealed by Visual Analog Scale. - Cheng, Bing; Xiang, Xi; Dai, Xiangrong; Zou, Yu; Zhang, Xiaojuan; Zhang, Yang (Journal of Speech, Language & Hearing Research, 2026)
Purpose: While the Visual Analog Scale (VAS) has revealed gradient perception in segmental speech sounds, its application to lexical tones, a critical yet understudied suprasegmental feature, has been absent. This study investigated lexical tone categorization using VAS, directly comparing it with traditional two-alternative forced-choice (2AFC). Method: Eighty-four native speakers of Mandarin Chinese categorized an 11-step fundamental frequency (F0) continuum from Mandarin Tone 1 to Tone 2 in both tasks. Four-parameter logistic functions yielded slope (categorization sharpness) and response variability. Within-category sensitivity was quantified from VAS responses. Results: Paired Wilcoxon signed-ranks test showed significantly shallower slopes (p < .001, r = .76) and lower variability (p < .001, r = .87) in VAS versus 2AFC. One-sample t tests confirmed that listeners discriminated fine-grained differences within categories, with within-category sensitivity reliably exceeding zero; left: M = 0.043, SD = 0.026, t(83) = 15.13, p < .001; right: M = 0.040, SD = 0.022, t(83) = 17.02, p < .001. Crucially, slope and response variability were weakly correlated in VAS (ρ = .27, p < .05) but strongly negatively correlated in 2AFC (ρ = −.67, p < .001). Moreover, response variability correlated significantly across tasks (ρ = .40, p < .001), while slopes did not. Conclusions: These findings provide the converging evidence that gradient aspects of perception are also observable at the suprasegmental level and illustrate how VAS can serve as a sensitive tool for probing lexical tone categorization. The dissociation between task-dependent gradiency and stable response variability helps reconcile apparent conflicts in the categorical perception literature, suggesting that these conflicts may stem from methodological constraints rather than genuine theoretical disagreements.